PRAGMATICS OF WHATSAPP MESSAGING BETWEEN STUDENT AND LECTURER - Novalita Pradnya Paramitha (JURNAL KONFIKS, 2021)
Pragmatics as a study of context-bound language can be useful for analysing meaning and attitudinal stance of a certain text. This study aims to scrutinize the pragmatic elements within Whatsapp messaging between the student and lecturer. The data source is a Whatsapp conversation between a student (the researcher’s friend) and his lecturer from April 2019 until January 2021. Then, the messages are analysed by the pragmatic theories of politeness, implicature, and presupposition; based on what pragmatic aspects observed within the conversation. The result shows that politeness is uttered by both the student and lecturer to gain solidarity and respect one another’s freedom. Implicature is for the lecturer to encourage the student in either academic field and pursuing information. Meanwhile, presupposition is performed by the student as the strategy to meet the lecturer in the near time. Keywords: Pragmatics, Whatsapp messaging, meaning, strategy.